PERANCANGAN SISTEM PENGAMAN BUSBAR 150 KV MENGGUNAKAN RELE DIFERENSIAL DI GARDU INDUK SANUR - Fauzi, Ahmad; Dyana Arjana, Gede; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUM, 2020)
Sanur substation has an important role to fulfill electricity consumption in the Sanur area and parts of the city of Denpasar. Bursbar is very important part of the performance of a substation. failures that occur on the busbar can result in widespread blackouts that disrupt the continuity of the flow of electric power. A sensitive, selective and fast busbar protection system is needed to prevent widespread blackouts. This research is designed to design dual 150 kV busbar protection using differential relays. The power flow and short circuit current in Sanur substation in this study were analyzed using simulation of load flow and short circuit with computer software. Current calculation as the basis for designing and setting differential relay settings as busbar protection is carried out by the Merz price calculating current method, all currents entering and leaving the secured equipment, compared to each other. The busbar protection system using differential relays was successfully designed with a pick up current setting of 0.88 A for busbar A and 1.046 A for busbar B, as well as breakpoints 6 A, slope1; 30%, slope2; 135%, and zero seconds working time for both relays the. The differential relay designed is able to isolate busbar failures more sensitive, more selective, and faster with a clearing time of 0.035 seconds compared to the existing condition protection system with a clearing time of 1.185 seconds.